EXPLORING FOOD CHEMISTRY IN NUTRITION: A FOCUSED REVIEW - P Priyadharshini; K. Karthick; R Lavanya; Palthangam Ganesan; Maram Soumya Sree (The Bioscan, 2025)
Food chemistry plays a pivotal role in understanding the relationship between food components and human nutrition. This focused review examines the fundamental chemical constituents of foods—including macronutrients, micronutrients, and bioactive compounds—and their transformations during processing, storage, and digestion. Emphasis is placed on how these chemical changes influence nutrient bioavailability, flavor, safety, and overall health outcomes. Recent advances in analytical techniques and molecular nutrition have enhanced insights into nutrient interactions, metabolic pathways, and the impact of dietary chemicals on human physiology. By bridging food chemistry and nutrition science, this review highlights current challenges and future directions for optimizing diet quality and developing functional foods aimed at improving public health.